2022
DOI: 10.1002/adfm.202206936
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiber Aerogels with Precision Macrochannels and LL‐37‐Mimic Peptides Synergistically Promote Diabetic Wound Healing

Abstract: Fast healing of diabetic wounds remains a major clinical challenge. Herein, this study reports a strategy to combine nanofiber aerogels containing precision macrochannels and the LL‐37‐mimic peptide W379 for rapid diabetic wound healing. Nanofiber aerogels consisting of poly(glycolide‐co‐lactide) (PGLA 90:10)/gelatin and poly‐p‐dioxanone (PDO)/gelatin short electrospun fiber segments are prepared by partially anisotropic freeze‐drying, cross‐linking, and sacrificial templating with 3D printed meshes, exhibitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…The efficacy of similar aerogel types has been demonstrated in prior studies. 58,69 However, the present study delves into the effect of the gradual release of Cu 2+ from CuHARS embedded within the aerogels. This investigation explores their roles in fostering angiogenesis and delivering a short-term burst of antibacterial effect.…”
Section: Characterization Of Cuhars-embedded Poly(ecaprolactone) (Pcl...mentioning
confidence: 94%
“…The efficacy of similar aerogel types has been demonstrated in prior studies. 58,69 However, the present study delves into the effect of the gradual release of Cu 2+ from CuHARS embedded within the aerogels. This investigation explores their roles in fostering angiogenesis and delivering a short-term burst of antibacterial effect.…”
Section: Characterization Of Cuhars-embedded Poly(ecaprolactone) (Pcl...mentioning
confidence: 94%
“…42 Previous studies also have indicated that the anti-inflammatory ability of LL-37 prevents exaggerated response to damage the infected tissues, since LL-37 also enhances the acute protective activation of innate immune system to promote the early control and clearance of infection through leukocyte recruitment and chemokines production (IL-1β, GRO-α, and IL-8). 43,44 The capacity that LL-37 helps to orchestrate the immune response to infection is essential for the diabetic wound healing. In this study, the delivery of LL-37 in the PACDFe@LL-37 hydrogel system could markedly induce macrophage polarization toward the M2 phenotype, inhibit pro-inflammatory cytokines, and provide a local anti-inflammatory microenvironment for wound healing.…”
Section: Pacdfe@ll-37 M2 Macrophage Polarization In Vitromentioning
confidence: 99%
“…In a study by John et al, a PLGA/GEL fiber aerogel containing the LL-37-mimic peptide W379 enhanced proliferation and migration of keratinocytes and fibroblasts, while the introduction of macrochannels within the aerogel improved cell penetration. Moreover, the patterned macrochannels together with the incorporation of W379 greatly increased the healing time of diabetic wounds through re-epithelization by upregulating p38 mitogen-activated protein kinase expression [48]. Membranes from living cells have attracted attention as a new way of improving the bioactivity of living materials.…”
Section: Poly(lactic-co-glycolic Acid) (Plga)mentioning
confidence: 99%